Omkring romanen Kongens Fald og dens illustratorer: Gudmund Hentze, Valdemar Andersen og Aage Sikker Hansen - Jørgensen, Aage (Passage - Tidsskrift for litteratur og kritik, 2022)
Jensen’s novel has been published in a string of different editions, drawing on different illustrators. In this article, Jørgensen examines the collaborations between Jensen and the key illustrators of the novel: Gudmund Hentze, who in 1900-1901 provided covers for the three volumes that the novel originally was published in; Valdemar Andersen, famous for his 1906 portrait of Jensen, who illustrated the second edition of the novel in 1913; and Aage Sikker Hansen, who was the first to fully illustrate the novel as it was published in relation to Jensen’s Nobel Prize award in 1944.